The forever tree - Surratt, Tereasa; Lukas, Donna; Slater, Nicola (New York : Crown Books for Young Readers, 2018)
"When a beloved tree gets sick, the human and animal communities work together to give it a new life."--
Keywords: Trees -- Juvenile fiction; Forest animals -- Juvenile fiction; Communities -- Juvenile fiction; Picture books